2018
DOI: 10.1038/s41598-018-21036-2
|View full text |Cite
|
Sign up to set email alerts
|

Reducing risk and improving maternal perspective-taking and empathy using virtual embodiment

Abstract: The ability to perspective-take (cognitive awareness of another’s state) and empathise (emotional/affective response) are important characteristics for sensitive, co-operative and constructive parenting, which assists in developing adaptive functioning for children. For the first time, immersive virtual reality was used to place parents in the position of a child in order to assess impact on perspective-taking and empathy. This novel study was conducted with 20 non-high risk Spanish mothers (a pilot study with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 44 publications
0
59
0
2
Order By: Relevance
“…Research has shown that even when the virtual body has a different age, gender or race, the body 77 ownership illusion leads people to take on the perspective and characteristics of the virtual character 78 (Banakou et al, 2013;Hamilton-Giachritsis et al, 2018). This type of training has also been utilized in 79 individuals with a reduced ability to take on others' perspectives, such as violent offenders (Seinfeld et 80 al., 2018).…”
mentioning
confidence: 99%
“…Research has shown that even when the virtual body has a different age, gender or race, the body 77 ownership illusion leads people to take on the perspective and characteristics of the virtual character 78 (Banakou et al, 2013;Hamilton-Giachritsis et al, 2018). This type of training has also been utilized in 79 individuals with a reduced ability to take on others' perspectives, such as violent offenders (Seinfeld et 80 al., 2018).…”
mentioning
confidence: 99%
“…In VR it is possible to give people the illusion that they have another body (Yee et al, 2009;Slater et al, 2010), and that their body has changed in some fundamental way. For example, adults can have the illusion of having a child body (Banakou et al, 2013), or white people a black body (Peck et al, 2013;Banakou et al, 2016), and these experiences change the participants-for example parents changing their behavior toward their children (Hamilton-Giachritsis et al, 2018), white people becoming more (Groom et al, 2009) or less implicitly biased against black (Maister et al, 2015), domestic violence offenders improving their recognition of fear in the faces of women after being embodied as a woman subject to abuse by a virtual man (Seinfeld et al, 2018), and so on. Scientific research has tended to explore positive benefits such as these.…”
Section: After-effectsmentioning
confidence: 99%
“…Bei diesen Ansätzen wird versucht, mit Hilfe von VR emotionales Erleben zu vertiefen und so therapeutische emotionale Veränderungen anzustoßen. In eine ähnliche Richtung geht die Nutzung des Embodiment zur Modifikation von Interaktionsmustern mit sich selbst und anderen [55,56]. "Embodiment" bezeichnet eine VR-Methode, bei der die Nutzer eine neue Perspektive auf sich und die Umwelt erleben, indem sie in der VR-Simulation einen Körper zugewiesen bekommen, der von ihrem eigenen abweicht (z.…”
Section: Weitere Anwendungenunclassified
“…"Embodiment" bezeichnet eine VR-Methode, bei der die Nutzer eine neue Perspektive auf sich und die Umwelt erleben, indem sie in der VR-Simulation einen Körper zugewiesen bekommen, der von ihrem eigenen abweicht (z. B. anderes Lebensalter, anderes Geschlecht, andere Hautfarbe [56,57]). Die Akzeptanz fremder oder simulierter Körperteile in das eigene Körperbild ist in der Psychologie umfassend untersucht worden.…”
Section: Weitere Anwendungenunclassified